Interventions promoting recovery from depression for patients transitioning from outpatient mental health services to primary care: Protocol for a scoping review. - Anne Sofie Aggestrup; Frederik Martiny; Maria Faurholt-Jepsen; Morten Hvenegaard; Robin Christensen; Annette Sofie Davidsen; Klaus Martiny (PLoS ONE)
Introduction Patients with severe Major Depressive Disorder (MDD) have an increasing risk of new psychiatric hospitalizations following each new episode of depression highlighting the recurrent nature of the disorder. Furthermore, patients are not fully recovered at the end of their treatment in outpatient mental health services, and residual symptoms of depression might explain why patients with MDD have a high risk of relapse. However, evidence of methods to promote recovery after discharge from outpatient mental health services is lacking. The proposed scoping review aims to systematically scope, map and identify the evidence and knowledge gaps on interventions that aims to promote recovery from MDD for patients transitioning from outpatient mental health services to primary care. Materials and methods The proposed scoping review will follow the latest methodological guidance by the Joanna Briggs Institute (JBI) in tandem with the Preferred Reporting Items for Systematic reviews and Meta-Analysis-extension for Scoping Reviews (PRISMA-ScR) checklist. The review is ongoing. Four electronic databases (Medline via PubMed, PsycINFO, CINAHL, and Sociological Abstracts) were systematically searched from 20 January 2022 till 29 March 2022 using keywords and text words. The review team consists of three independent screeners. Two screeners have completed the initial title and abstract screening for all studies retrieved by the search strategy. Currently, we are in the full text screening phase. Reference lists of included studies will be screened, and data will be independently extracted by the review team. Results will be analyzed qualitatively and quantitatively. Discussion The chosen methodology is based on the use of publicly available information and does not require ethical approval. Results will be published in an international peer reviewed scientific journal, at national and international conferences and shared with relevant authorities. Registration A pre-print has been registered at the medRxiv preprint server for health sciences (doi.org/10.1101/2022.10.06.22280499).